Model problem based learning meningkatkan kemampuan reading comprehension siswa: meta-analisis - Putu Sudarmika (Indonesian Journal of Educational Development, 2021)
Proses pembelajaran merupakan interaksi langsung yang terjadi antara guru dan para siswa untuk mencapai tujuan dari pembelajaran. Pencapaian hasil belajar Bahasa Inggris yang masih rendah pada setiap tingkatan dan jenjang Pendidikan, dapat dijadikan sebagai salah satu indikasi masih rendahnya kemampuan membaca dalam Bahasa Inggris pada siswa. Dimana masih terjadi kesenjangan kemampuan siswa dalam hal membaca teks dalam Bahasa Inggris masih dibawah batasan minimal KKM Bahasa Inggris. Untuk mengetahui pengaruh model pembelajaran problem-based learning meningkatkan kemampuan reading comprehension siswa. Penelitian ini menggunakan metode meta-analisis, dengan menggunakan artikel dengan desain pre-test and post-test control group design. Penelitian ini dilakukan dari bulan juli sampai dengan bulan oktober 2021 di Denpasar dengan kriteria inklusi dan eklusi terpilih 6 buah artikel sesuai kriteria. Data dianalisis dengan software JASP V-0.11, untuk mencari besar nilai effect size artikel penelitian. Hasil uji heterogenitas nilai Q = 4.667 dan nilai p = 0,456. Sehingga nilai p> 0,05 = 0.458 > 0.05. Model penggabungan effect size digunakan model fixed effect. hasil uji Egger,s Test, nilai p = 0,778 > 0.05 berarti Funnel Plot Simetris. Dan tidak terjadi bias publikasi. Kesimpulan problem based learning model pada hasil pembelajaran reading comprehension, dimana nilai effect size gabungan atau summary effect menghasilkan effect size sebesar katagori sedang. The learning process is a direct interaction between teachers and students, to achieve the objectives of learning. The achievement of English learning outcomes is still low at education levels. It indicates that English reading ability of the students are still low. There is still a gap of students' abilities in English reading comprehension below the minimum KKM English limit. To determine the effect of the problem-based learning model in improving students' reading comprehension skills, this study uses a meta-analysis method, using articles with a pre-test and post-test control group design. This research was conducted from July to October 2021 in Denpasar with inclusion and exclusion criteria selected 6 articles according to the criteria. The research data were analyzed using JASP V-0.11 software to calculate the effect size value of the articles that became the research sample. The results of the heterogeneity test of the value of Q = 4.667 and the value of p = 0.458. So, the value of p> 0.05 = 0.458 > 0.05. The combined effect size model uses a fixed effect model. the results of the Egger's Test, the value of p = 0.778 > 0.05 means that the Funnel Plot is Symmetrical. And there is no publication bias. The conclusion of the problem-based learning model on reading comprehension learning outcomes is the combined effect size value or summary effect produces an effect size of the medium category.